Unraveling the mystery of the hygiene hypothesis through Helicobacter pylori infection - Matsushima, Kouji; Nagai, Shigenori (The Journal of Clinical Investigation, 2012)
Epidemiological studies have revealed an inverse association between Helicobacter pylori infection and the incidence of allergic asthma. This association is consistent with the hygiene hypothesis, which posits that exposure to microbes early in life prevents the later development of allergic diseases, and has been reproduced in mouse models of asthma. In this issue of the JCI, Oertli and colleagues report that H. pylori infection in neonates elicits tolerogenic DCs that produce IL-18, which drive the generation of Tregs that subsequently protect the mice from allergic asthma. This finding strengthens the intriguing link between pathogen exposure and allergic disease.